An In vitro Investigation of the Potential Synergistic Effect of 3-Hydrazinoquinoxaline-2-Thiol and Thymoquinone’s against Methicillin Resistant Staphylococcus aureus (MRSA) - Karem Ibrahem; Wafaa Alhazmi; Hanouf A. Niyazi; Hatoon A. Niyazi; Bandar Saleh; Tariq Ekhmimi; Jawahir A. Mokhtar; Dalya Attallah; Mohammed Bazuhair; Khalil Alkuwaity; Ahmad Sait; Mohammed Mufrrih; et al. (Journal of Pure and Applied Microbiology)
Bacterial infections continue to pose a significant global health threat, further intensified by the increasing prevalence of antibiotic resistance. Methicillin-resistant Staphylococcus aureus (MRSA) poses significant threats, especially in healthcare settings around the world. Conventional treatments face some limitations due to development of antimicrobial resistance, emphasizing the urgent need to explore alternative treatment strategies. In this study, we propose the potential synergistic activity of thymoquinone and 3-hydrazinoquinoxaline-2-thiol (3HT) to combat MRSA infections. The minimum inhibitory concentrations (MICs) of both thymoquinone and 3HT were assessed across twenty-two clinical MRSA strains. Thymoquinone demonstrated the minimum inhibitory concentration (MIC) values range between 8 and 128 µg/ml., while 3HT exhibited MIC levels varying from 16 to 32 µg/ml. Moreover, the checkerboard-assay was utilized to evaluate the integration of the following antimicrobial agents; thymoquinone and 3HT. Thymoquinone and 3HT bind to PBP2a leading to reduction in MRSA antimicrobial resistance via significantly disrupting its structure and function. Our study reveals an in-vitro synergistic interaction between these compounds with a fractional inhibitory concentration index (FICI) less than 0.5 against different isolated MRSA strains. While further research is necessary, our findings offer a promising approach for developing new effective MRSA treatments.